Adherence to clozapine vs. other antipsychotics in schizophrenia. (2nd August 2020) - Takeuchi, H.; Borlido, C.; Sanches, M.; Teo, C.; Harber, L.; Agid, O.; Remington, G.
Abstract : Background: To date, there have been no studies evaluating adherence to clozapine with electronic adherence monitoring (EAM) such as the Medication Event Monitoring System (MEMS ® ). Methods: In outpatients with schizophrenia, we conducted a 3‐month prospective study investigating antipsychotic adherence with EAM (eCAP ® ). Participants were treated with different oral antipsychotics, including clozapine, and blind to EAM monitoring; all were on antipsychotic monotherapy administered once daily. Outcome measures included adherence rate, missed dose, and medication gap. Adherence trajectory patterns were also analyzed for clozapine vs. other antipsychotics collectively. Results: A total of 111 patients were included in the study; 33 and 78 patients received clozapine or other antipsychotics, respectively. Adherence rates, defined as proportion of days that the subject took the medication at the prescribed time ± 3 h and proportion of subjects with ≥80% adherence, were numerically higher in patients receiving clozapine vs. other antipsychotics (72.0% vs. 65.1%, P = 0.10; 49.5% vs. 35.7%, P = 0.11, respectively). Along similar lines, some of the missed dose and medication gap outcomes were significantly better in patients receiving clozapine vs. other antipsychotics. Three adherence trajectory patterns were identified for both clozapine and other antipsychotics, with two shared by both groups (i.e., low adherence with a slight decrease over time; high and stable adherence). Conclusion: Findings suggest that in patients with schizophrenia clozapine adherence is at least comparable, if not slightly better, compared with other antipsychotics.